Selective Cytotoxicity of Single and Dual Anti-CD19 and Anti-CD138 Chimeric Antigen Receptor-Natural Killer Cells against Hematologic Malignancies - Sudjit Luanpitpong; Jirarat Poohadsuan; Phatchanat Klaihmon; Surapol Issaragrisil (Journal of Immunology Research)
Natural killer (NK) cells are part of the first line of defense that rapidly respond to malignant transformed cells. Chimeric antigen receptor- (CAR-) engineered NK cells, although are still at the preliminary stage, have been shown to be alternative to CAR-T cells, mainly due to the absence of graft-versus-host disease and safer clinical profile. Allogeneic human NK cell line NK-92 cells, equipped by CAR, are being developed for clinical applications. Herein, we designed third-generation CARs, optimized the production protocol, and generated CAR-NK-92 cells, targeting CD19 and/or CD138 antigens that employ CD28, 4-1BB, and CD3ζ signaling, with >80% CAR expression, designated as CD19-NK-92, CD138-NK-92, and dual-NK-92 cells. The generated CAR-NK-92 cells displayed high and selective cytotoxicity toward various corresponding leukemia, lymphoma, and multiple myeloma cell lines in vitro. Multitargeting approach using a mixture of CD19-NK-92 and CD138-NK-92 cells was also evaluated at various ratios to test the idea of personalized formulation to match the patients’ antigen expression profile. Our data indicate that increasing the ratio of CD19-NK-92 to CD138-NK-92 could improve NK cytotoxicity in leukemia cells with a relatively higher expression of CD19 over CD138, supporting the personalized proof of concept. This information represents the basis for further in vivo studies and future progress to clinical trials.